2019
DOI: 10.1007/s00217-019-03257-5
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular biosynthesis of melatonin and other indolic compounds in Saccharomyces and non-Saccharomyces wine yeasts

Abstract: Certain bioactive compounds that derive from tryptophan have been determined in 33 fermented foods, which suggests that the role of yeast is putative in origin. Melatonin is a 34 neurohormone in humans that plays an important role in health. The activity of other 35 compounds, such as 3-indoleacetic acid, has been recently highlighted, and interest in 36 elucidating the conditions of their production has grown. 37 However, the biosynthesis of melatonin by yeasts remains unclear to a large extent. 38 Therefore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 24 publications
0
23
0
Order By: Relevance
“…It would seem that melatonin synthesis most strongly depends on the yeast strain/species, and also on the cell metabolic state (62), but a clear condition that produces increased melatonin is still unknown. During the alcoholic fermentation of natural grape must, the production of indolic compounds largely depends on the used cultivar and fermentation time (49).…”
Section: Fig 1 Evolution Of Publications On Related Topics Comparedmentioning
confidence: 99%
See 1 more Smart Citation
“…It would seem that melatonin synthesis most strongly depends on the yeast strain/species, and also on the cell metabolic state (62), but a clear condition that produces increased melatonin is still unknown. During the alcoholic fermentation of natural grape must, the production of indolic compounds largely depends on the used cultivar and fermentation time (49).…”
Section: Fig 1 Evolution Of Publications On Related Topics Comparedmentioning
confidence: 99%
“…This compound is formed through the esterification of tryptophan, but what role it can play remains unclear. Several yeast species, including S. cerevisiae and non-Saccharomyces species, have been reported as being capable of releasing tryptophan ethyl ester under enological conditions, and have been found in different wines (59,62,67,68). Vitalini et al (45) reported the presence of three MIs in wines and balsamic vinegars, while Fracassetti et al (27) more recently identified up to five MIs by UHPLC/ESI-QTRAP.…”
Section: Fig 1 Evolution Of Publications On Related Topics Comparedmentioning
confidence: 99%
“…Since Sprenger et al [ 5 ] initially related melatonin production to Saccharomyces cerevisiae , several studies have reported the ability of yeasts to synthetize melatonin during alcoholic fermentation, with levels in wine ranging bewteen 0.3–1800 nM [ 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. Little information on melatonin biosynthesis in yeast is available.…”
Section: Introductionmentioning
confidence: 99%
“…Melatonin is a bioactive molecule that has been recently described to have a positive role against oxidative stress [ 11 , 12 ] and UV stress [ 13 ] in yeasts. In addition to its protective role, melatonin is produced by yeast during the winemaking process [ 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%